Minat Baca Mahasiswa Pada Perpustakaan Digital Di Masa Pandemi Covid-19 - Victoria Ratu Ester; Nonsihai Nonsihai; Rinto Alexandro; Sri Rohaetin; Susi Sukarningsi; Hendrowanto Nibel; Susan Daniel (FKIP, Universitas Palangka Raya, 2022)
The research in this thesis is motivated by the importance of reading for students. Students as Indonesian human resources are needed ideas and opinions to build this country. The quality of human resources is strongly related to the interest in reading that students have. Reading habits are not only related to the teaching and learning process, but can also shape the personality of the individual by living the reading results. The discussion is The Interest of Reading Students of the Class of 2017 in the Digital Library during the Covid-19 Pandemic in the Economic Education Study Program of FKIP University of Palangka Raya. This study aims to express students' reading interest in completing lecture assignments by using digital libraries during the Covid-19 pandemic di Economic Education Study Program FKIP University of Palangka Raya. This research method uses qualitative approach, with research methods that are dequalitatively curative. This study aims to describe the results of data processing in the form of words, images that occur in the field that are natural and discovery in accordance with the phenomenon and actual circumstances. The results of the study conducted by The Interest in Reading Students of the Class of 2017 at the Digital Library During the Covid-19 Pandemic inthe Economic Education Study Program of FKIP University of Palangka Raya, this is shown by the results ofinterviews that researchers have drawn the conclusion that the interest in reading students during the Covid-19 Pandemic at the Digital Library of Palangka Raya University is still relatively low judging by the duration spent reading and the number of student visits to digital libraries. The low interest in reading students due to the obstacles experienced when accessing digital libraries yang become obstacles in accessing the first digital library network because this network is very important if there is no internet network then we can not access the digital library,then need media as a place to access it such as mobile phones, tablets, and also computers/laptops